Eating behavior during dexamethasone treatment in children with acute lymphoblastic leukemia. Issue 12 (9th June 2017) - Warris, Lidewij T.; van den Akker, Erica L.T.; Bierings, Marc B.; van den Bos, Cor; Aarsen, Femke K.; Zwaan, Michel C.; Tissing, Wim J.E.; Veening, Margreet A.; Pieters, Rob; van den Heuvel‐Eibrink, Marry M.
Abstract: Background and aim: Large prospective studies on dexamethasone‐induced changes in eating behavior, energy, and nutrient intake are lacking in pediatric acute lymphoblastic leukemia (ALL). We prospectively studied eating behavior, energy, nutrient intake, and the effect on leptin and adiponectin levels during dexamethasone administration in children with ALL. Patients: Parents of patients with ALL (3–16 years) completed a dietary diary for their child during 4 days of dexamethasone (6 mg/m 2 ) administration. Energy intake and nutrient intake (energy percentage = E%) were assessed and compared with the recommended intake. The Dutch Eating Behavior Questionnaire for Children was completed before start and after 4 days of dexamethasone administration by patients of 7–12 years of age. Fasting leptin and adiponectin levels were also measured before start and after 4 days of dexamethasone administration. Results: Energy intake per day(kcal) (N = 44) increased significantly during dexamethasone ( median day 1: 1, 103 (717–1, 572) versus day 4: 1, 482 (1, 176–1, 822), P < 0.01), including an increase in total protein, fat, saturated fat, carbohydrate, and sodium intake. Intake of saturated fat (median day 4: 12 E%) and salt (median day 4: 1.9 g/day) exceeded the healthy range for age and gender. With respect to eating behavior, dexamethasone significantly decreased restrained eating ( P = 0.04). Leptin levels as well as adiponectin levels increased significantly during the dexamethasone course. Conclusions: Four days of dexamethasone treatment significantly increased energy intake, including excessive saturated fat and salt intake, and changed eating behavior in children with ALL. Nutritional and behavioral interventions during dexamethasone treatment are recommended to stimulate a healthy lifestyle.